2013
DOI: 10.5539/gjhs.v6n2p155
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Fruit and Vegetable Consumption among Saudi University Students

Abstract: The positive benefits of consumption fruit and vegetable are well documented in studies of health and body weight maintain. A cross sectional study was conducted utilized street based survey among 960 female students at King Faisal University in AL-Hasa, Saudi Arabia, to investigate the daily consumption of fruits and vegetables and the psychosocial factors related to the consumption. Seventy-eight percent of students consuming <5 servings/day of fruit and vegetable with only 22% of them consuming ≥5 servings/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
6
33
2
2
Order By: Relevance
“…Low intake of fruits and vegetables [13,15,17,18,20,23,26,27,29,[30][31][32][33][34][35][36][38][39][40][41][45][46][47][48][49][50][51] 69.0 87.5…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Low intake of fruits and vegetables [13,15,17,18,20,23,26,27,29,[30][31][32][33][34][35][36][38][39][40][41][45][46][47][48][49][50][51] 69.0 87.5…”
Section: Resultsmentioning
confidence: 99%
“…Yet, other studies found that both genders had low intake of fruits and vegetables [17,40]. Studies of females only also found low intake of fruits and vegetables by most, and the need to improve diet quality [24,31,36,41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this study, it is recommended that students develop the desire to consume vegetables and fruits, choose vegetables and fruits with less sugar and sodium, and buy the less costly fruit and vegetable choices. Besides, it is recommended for the respondents to prepare food with fresh vegetables and fruits in various ways using different recipes during meal times and refreshments [16]. Other than that, fruits can usually be eaten as refreshment or desserts after meals.…”
Section: Fruitsmentioning
confidence: 99%